Criminal libility of the doctor in the case of artificial resucitation - Grani, Moufida (Journal of Human Sciences, 2022)
One of the most sensitive and complex subjects in determining the time of death is the criminal responsibility for artificial resuscitation. In this case, opinions diverged, however, the protocol adopted to declare the time of death is brain death. In other words; the death of the brain stem, which has vital functions for human life. This phenomenon is irreversible because it is enough that this part stops functioning for a few minutes unlike other vital parts that can be saved by artificial resuscitation, It is therefore not possible to hold accountable and prosecute the doctor who provides the necessary care to the patient in a critical condition and who removes the devices after having noticed the complete shutdown of the brain cells even if he observes that other vital organs are still functioning such as the heart or lungs,Otherwise; if the physician removes the artificial resuscitation equipment before he becomes aware of the brain death, he will be considered responsible for the death of the patient, even if it is done by mistake or if his act is motivated by compassion towards the patient.